Microbial Degradation of Lobster Shells to Extract Chitin Derivatives for Plant Disease Management - Ilangumaran, Gayathri; Stratton, Glenn; Ravichandran, Sridhar; Shukla, Pushp S.; Potin, Philippe; Asiedu, Samuel; Prithiviraj, Balakrishnan (Frontiers in Microbiology, 2017)
Biodegradation of lobster shells by chitinolytic microorganisms are an environment safe approach to utilize lobster processing wastes for chitin derivation. In this study, we report degradation activities of two microbes, “S223” and “S224” isolated from soil samples that had the highest rate of deproteinization, demineralization and chitinolysis among ten microorganisms screened. Isolates S223 and S224 had 27.3 and 103.8 protease units.mg-1 protein and 12.3 g.ml-1 and 11.2 g.ml-1 of calcium in their samples, respectively after one week of incubation with raw lobster shells. Further, S223 contained 23.8 g.ml-1 of N-Acetylglucosamine on day three, while S224 had 27.3 g.ml-1 on day seven of incubation with chitin. Morphological observations and 16S rDNA sequencing suggested both the isolates were Streptomyces. The culture conditions were optimized for efficient degradation of lobster shells and chitinase ( 30 kDa) was purified from crude extract by affinity chromatography. The digested lobster shell extracts induced disease resistance in Arabidopsis by induction of defense related genes (PR1 > 500 fold, PDF1.2 > 40 fold) upon Pseudomonas syringae and Botrytis cinerea infection. The study suggests that soil microbes aid in sustainable bioconversion of lobster shells and extraction of chitin derivatives that could be applied in plant protection.